Modelling collaboration of primary and secondary care for children with complex care needs: long-term ventilation as an example - Brenner, Maria (My University, 2019)
Children dependent on long-term ventilation need the planning, provision and monitoring of complex services generally provided at home by professionals belonging to different care settings. The collaboration among professionals improves the efficiency and the continuity of care especially when treating children with complex care needs. In this paper, the Unified Modelling Language (UML) has been adopted to detect the variety of the patterns of collaboration as well as to represent and compare the different processes of care across the 30 EU/EEA countries of the MOCHA project. Conclusion: Half of the analysed countries have a multidisciplinary team with different degrees of team composition, influencing organisational features such as the development of the personalised plan as well as the provision of preventive and curative services. This approach provides indications on the efficiency in performing and organising the delivery of care in terms of family involvement, interactions among professionals and availability of ICT. What is known: • Children with CCNs require a coordination of efforts before and after discharge in a continuum of care delivery dependent on the level of integrated care solutions adopted at country level. What is new: •The adoption of a business process method contributes to perform a cross-country analysis highlighting the variability of team composition and its influence on the delivery of care. • This approach provides indications on the efficiency in performing and organising the delivery of care in terms of family involvement, interactions among professionals and availability of ICT.
Keywords: long-term home ventilation; children; complex care needs; Process modelling; UML; Professional collaboration; LTV; Multidisciplinary team